2015
DOI: 10.1111/cob.12127
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviours are different in youth with obesity and severe obesity

Abstract: Objective The study purposes were to: 1) investigate eating behaviors among patients in a pediatric weight management clinical practice, and 2) compare eating behavior phenotypes between children with severe obesity and obesity. Method This was a retrospective cross-sectional study using data collected during clinical encounters. Participants were included if they were 2-12 years old, had a BMI ≥95th percentile, and if a parent/guardian completed the Child Eating Behavior Questionnaire (CEBQ). Results Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…We observed associations between overeating and rapid eating (uncontrolled eating) and the degree of obesity at enrolment, while meal skipping and emotional eating was not associated with the degree of obesity in this study. This is in line with a small study of 112 children with obesity that found a higher degree of obesity among those exhibiting uncontrolled eating, and partly with another small study of children with obesity, where the presence of emotional eating and uncontrolled eating increased with increasing degree of obesity in girls . That we did not find this association between emotional eating and degree of obesity may be due to the larger number of children and adolescents in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed associations between overeating and rapid eating (uncontrolled eating) and the degree of obesity at enrolment, while meal skipping and emotional eating was not associated with the degree of obesity in this study. This is in line with a small study of 112 children with obesity that found a higher degree of obesity among those exhibiting uncontrolled eating, and partly with another small study of children with obesity, where the presence of emotional eating and uncontrolled eating increased with increasing degree of obesity in girls . That we did not find this association between emotional eating and degree of obesity may be due to the larger number of children and adolescents in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Disturbed eating behaviours are traditionally categorised into three domains: cognitive restraint, emotional eating and uncontrolled eating . In children and adolescents, these domains have been defined as follows: cognitive restraint as a conscious restriction of food intake to avoid gaining weight; emotional eating as the tendency to eat in response to emotions; and lastly, uncontrolled eating as a tendency to eat more than usual and a concurrent feeling of loss of control . While this definition of uncontrolled eating resembles the diagnosis of binge eating disorder, clinical diagnoses of eating disorders are rarely made before adolescence …”
mentioning
confidence: 99%
“…Emotional overeating referred to eating when experiencing negative emotions or boredom (e.g., “My child eats more when anxious” “My child eats more when annoyed”) (Wardle et al, 2001). Lower levels of satiety responsiveness and higher levels of food responsiveness and emotional overeating have been associated with child weight status (Carnell & Wardle, 2008; Dornoff et al, 2015; Frankel et al, 2014; Gardner et al, 2015; Gross et al, 2016; Mallan et al, 2013; Santos et al, 2011; Sleddens et al, 2008; Spence et al, 2011; Viana et al, 2008; Webber et al, 2009). Responses were scored on a 1 to 5 scale (never to always).…”
Section: Methodsmentioning
confidence: 99%
“…Factor structure, test-retest reliability, and internal consistency were described in a sample of predominately white families in the United Kingdom (Wardle et al, 2001). The CEBQ has been used successfully in multiple samples of ethnically diverse children (Dornoff et al, 2015; Frankel et al, 2014; Gardner et al, 2015; Gross et al, 2016; Mallan et al, 2013; Santos et al, 2011; Viana et al, 2008). Coefficient alphas were adequate in the current sample (0.68 for satiety responsiveness; 0.79 for food responsiveness; and 0.69 for emotional overeating).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation